Distribution Of Multipple Herbicide Resistant Eleusine indica L. Gaertn. An Oil Palm Estate In North Sumatera - ahmad bayu syahputra; Edison Purba Purba; Yaya Hasanah Hasanah (Jurnal Agroekoteknologi, 2016)
Goosegrass (Eleusine indica) in a block of oil palm Estate at Serdang Bedagai, North Sumatera had been controlled using glyphosate and paraquat for more than 26 years continuously. Recently, it had been reported that the two herbicides failed to control the population. The estate consists of 4000 Ha or 437 blocks which had slightly different history in weed management. The objective of this study was to determine the distribution Eleusine indica Resistant to glyphosate and paraquat in the oil palm estate. Seed of  E. indica were collected from each block and tested for resistant to glyphosate and paraquat at rate 480 g.a.i / ha and 300 g.a.i/ha consecutinely. A long with the seeds from the estate, seeds of E.indica susceptible to glyphosate and paraquat which had been confirmed were also germinated for a comparison. Results showed that 58 populations from the Adolina estate. 57 populations resistant of  glyphosate and 1 population moderate resistantce of glyphosate. And 55 populations resistantce to paraquat and 3 populations moderate resistantce to paraquat.Keywords: Eleusine indica, glyphosate, paraquat, resistance